The influence of financial ratios and companies size to predict conditions of financial distress: researches on companies listed on indonesian stock exchange for the period 2013-2017 - Dahlia Dahlia (The Accounting Journal of Binaniaga, 2021)
This research aims to determine the condition of financial distress by using the Indicator Current ratio, Debt to Equity ratio, Total Assets Turn Over and company size (SIZE) measured in the natural logarithm of Total Assets.The research period was 2013-2017 by dividing 2 groups of companies, namely between companies that suffered losses and companies that did not suffer losses. Data analysis, with Descriptive, Logistic Regression testing and Independent Sample T test. The results of the research obtained that the hypothesis for Current ratio and SIZE does not match the results; Total Assets Turn Over affects bankruptcy and Debt to equity ratio has no effect on bankruptcy.From the different tests obtained results there are significant differences between the group of companies in financial distress conditions and companies that are safe.Keywords: financial distress, current ratio, debt to equity ratio, total asset turn over, size, different test T test